Association between obesity and postoperative atrial fibrillation in patients undergoing cardiac operations: a systematic review and meta-analysis - Hernández, Adrian V. (2014)
In a systematic review and random effects meta-analysis, we evaluated whether obesity is associated with postoperative atrial fibrillation (POAF) in patients undergoing cardiac surgery. Eighteen observational studies that excluded patients with preoperative AF were selected until December 2011 (n=36,147). Obese patients had a modest higher risk of POAF in comparison to non-obese (OR 1.12, 95%CI 1.04-1.21, p=0.002). The association between obesity and POAF did not vary substantially by type of cardiac surgery, study design or year of publication. POAF was significantly associated with higher risk of stroke, respiratory failure, and operative mortality.